Penggunaan Media Pembelajaran IPS di Kelas MI Ma’arif 1 Pageraji Kecamatan Cilongok Kabupaten Banyumas Tahun Pelajaran 2014/2015 - Munadzir, Aris (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2019)
recipient (students) in the context of teaching and learning interactions. Learning mediais expected to be an intermediary to facilitate students' understanding of the subjectmatter. The purpose of this study was to determine the media used in social sciencelearning and how to use it in social science learning at MI Ma'arif NU 1 Pageraji, CilongokDistrict, Banyumas Regency, 2014/2015 academic year. The results of research from theuse of social science learning media at MI Ma'arif NU 1 Pageraji can 1) assist teachers indelivering subject matter and make it easier for students to understand the material, 2)in learning the teacher can use more than one media by considering its effectiveness,and 3) the teacher evaluates the use of the media to determine the effectiveness of themedia in the process of achieving learning objectives.